The legality of Arable Land Minimizes Disputes - Eliana Eliana; Aria Dimas Harapan; Reny Suryani; Sri Endah Indriawati (Asian Journal of Social and Humanities, 2023)
Realizing the legality of ownership of arable land can be obtained by the community by carrying out land registration referring to the Regulation of the Minister of Agrarian Affairs dated February 9, 1999 Number 3 of 1999 concerning Delegation of Authority for Granting and Cancellation of Decisions on State Land Rights continued with the PMNA/Head. BPN Number 4 of 1998 jo. KMNA/Ka.BPN Number 6 of 1998 concerning Guidelines for Determining income in the Granting of State Land Rights. Settlement of disputes over the ownership of arable land in Bogor Regency can be carried out through litigation or outside of litigation and in the case of arable land disputes in Bogor it can be resolved through peace through mediation. It is suggested that the government should schedule counseling on the legality of land ownership to the public so that ordinary people understand the legality process so that the community's economic level is stable and even becomes strong.